Menneskerettigheter og Den russisk-ortodokse kirke: opportunisme, autoritarianisme eller ortodoks nasjonalisme? - Haugen, Hans Morten (Nordisk Østforum, 2017)
Human Rights and the Russian Orthodox Church: Opportunism, Authoritarianism or Orthodox Nationalism? The Russian Orthodox Church (ROC) as a traditional majority church enjoys a privileged position in the Russian society. The current Russian regime has strengthened ROC’s position, and the alliance between the two has strengthened the emphasis on traditional values. With emphasis on the very nature of Orthodox Christianity, the article seeks to explain variations in ROC’s understanding of and receptiveness of human rights, emphasizing rights that protect certain groups of people, including refugees and minorities. Four explanations are identified: national heritage; whether new minorities are considered a threat to this legacy; how the church understands its relationship with the state; and the organizational structure of the church, influenced by the prevailing political culture. ROC has a self-understanding of being the keeper of the Russian national heritage, and is skeptical of influences other than those coming from the tradition and state. Relevant orthodox theological concepts are introduced as explanations: symphony (harmonious relationship between state and church), pomestnost (national embeddedness), sobornost (the self as part of the collective) and the teosis (also referred to as “bogochelovek”, human divinity).